2012
DOI: 10.1111/j.1467-9310.2011.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Value creation by knowledge‐based ecosystems: evidence from a field study

Abstract: A growing number of research and development‐driven companies are located in knowledge‐based ecosystems. Value creation by these ecosystems draws on the dynamics of single firms (interacting and partnering) as well as the ecosystem at large. Drawing on a field study of a Dutch high‐tech campus, two key sources of value creation are identified: (1) facilitation of the innovation process for individual companies and (2) creation of an innovation community. Furthermore, the coevolution of the ecosystem's business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(62 citation statements)
references
References 58 publications
0
57
0
5
Order By: Relevance
“……it's very difficult to network in that kind of situation” (p. 372). In contrast, Van der Borgh et al () report the benefits of informal activities or services, “I like networking via the Business Lounge. It's easy to get into contact with other people and companies, so that one can identify with the high tech campus” (p. 160).…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“……it's very difficult to network in that kind of situation” (p. 372). In contrast, Van der Borgh et al () report the benefits of informal activities or services, “I like networking via the Business Lounge. It's easy to get into contact with other people and companies, so that one can identify with the high tech campus” (p. 160).…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…In particular, they should not seek to follow ‘one‐size‐fits‐all recipes’ (Ebbekink & Lagendijk, ), but rather should try to assure the fit between the network's strategy and design – in terms of, for example, type of members, appropriability regimes and supports provided – with the type of firms, and in particular the innovation objectives and actual networking behaviour. In line with the findings of van der Borgh, Cloodt and Romme () to assure such a fit, policy makers and network managers are advised to engage in a close and continual dialogue not only with the potential but also the current network participants as their needs will most likely change over time.…”
Section: Discussionmentioning
confidence: 77%
“…We believe that these resource requirements are the driving force behind firms' choice both to join innovation networks in general and certain specific innovation networks in particular. Past research has shown that firms join innovation networks in order to learn and share experience, to gain novel ideas and information, to find potential partners for exchange and innovation, and to gain access to shared resources and facilities (Bessant et al., ; Paquin & Howard‐Grenville, ; Perry, ; van der Borgh, Cloodt & Romme, ). Still, to our knowledge, no studies has sought to explore the relation between the firm's decision to join a particular innovation network and its own profile.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations